Neglected gaps in improving the health, wellbeing, and care for sexual and gender minority young people living in low- and lower-middle- income countries: a scoping review - Cara Frances; Camille Garnsey; Jessica DeMulder (BMC, 2023)
Abstract Background There is a lack of reliable data on the size, characteristics, and experiences of sexual and gender minority (SGM) young people (ages 10-24) in low- and lower-middle- income countries (LMICs). This review examines the research conducted in the last thirteen years with and about SGM young people living in low-income settings and seeks to answer the question: What is known about the mental and physical health needs, safety, and wellbeing of SGM young people living in LMICs? Methods We conducted a scoping review informed by the methodological frameworks put forth by Arksey and O'Malley and the Joanna Briggs Institute. We systematically searched two general social science databases and one topic-specific database for peer-reviewed papers, of any research design, that included SGM young people or explored attitudes toward SGM young people in LMICs. We included papers that reported on factors influencing the health and wellbeing of SGM populations, including physical and mental health, healthcare-seeking behaviors, substance use, experiences of discrimination and/or stigma, experiences of violence and abuse (emotional, physical, and/or sexual), economically motivated paid sex practices, housing or economic security, and attitudes of others toward SGM populations. Results Of the 5,409 unique records identified, 79 papers drawing from data collected from 74 unique studies met the inclusion criteria. Only 50 of the 79 papers included SGM young people as participants, with just 13 focusing exclusively on SGM young people ages 10-24. The included papers were classified into three thematic groupings: attitudes toward SGM populations (n = 26), risks to health (n = 40), and experiences of stigma and discrimination (n = 13). Conclusion The findings indicate that the health and wellbeing of SGM young people in LMICs has been historically under-researched. While SGM young people have received more attention from researchers in recent years, the body of literature as a whole is disjointed and sparse, and often studies are about SGM young people, rather than with and for them. Our review highlights the need for more and better research, more accurate and disaggregated demographic data, and leadership and participation of SGM-led community-based organizations in the co-design of studies that focus on SGM young people.